Time and frequency domain analysis of physiological features during autonomic dysreflexia after spinal cord injury - Kirby, Ana Karina; Pancholi, Sidharth; Anderson, Zada; Chesler, Caroline; Everett, Thomas H.; Duerstock, Bradley S. (Frontiers in Neuroscience, 2023)
Autonomic dysreflexia (AD) affects about 70% of individuals with spinal cord injury (SCI) and can have severe consequences, including death if not promptly detected and managed. The current gold standard for AD detection involves continuous blood pressure monitoring, which can be inconvenient. Therefore, a non-invasive detection device would be valuable for rapid and continuous AD detection. In this study, we analyzed skin nerve activity (SKNA) and heart rate variability (HRV) parameters in the time and frequency domain to improve non-invasive and early AD detection. We found that SKNA features showed an increase approximately 18 seconds before the typical rise in systolic blood pressure, indicating the onset of AD in a rat model with upper thoracic SCI. Additionally, low-frequency components of SKNA in the frequency domain were dominant during AD, suggesting their potential inclusion in an AD detection system for improved accuracy. Utilizing SKNA measurements could enable early alerts to individuals with SCI, allowing timely intervention and mitigation of the adverse effects of AD, thereby enhancing their overall well-being and safety.